Streptococcus suis, an Emerging Drug-Resistant Animal and Human Pathogen - Palmieri, Claudio; Varaldo, Pietro E.; Facinelli, Bruna (Frontiers in Microbiology, 2011)
Streptococcus suis, a major porcine pathogen, has been receiving growing attention not only for its role in severe and increasingly reported infections in humans, but also for its involvement in drug resistance. Recent studies and the analysis of sequenced genomes have been providing important insights into the S. suis resistome, and have resulted in the identification of resistance determinants for tetracyclines, macrolides, aminoglycosides, chloramphenicol, antifolate drugs, streptothricin, and cadmium salts. Resistance gene-carrying genetic elements described so far include integrative and conjugative elements, transposons, genomic islands, phages, and chimeric elements. Some of these elements are similar to those reported in major streptococcal pathogens such as Streptococcus pyogenes, Streptococcus pneumoniae, and Streptococcus agalactiae and share the same chromosomal insertion sites. The available information strongly suggests that S. suis is an important antibiotic resistance reservoir that can contribute to the spread of resistance genes to the above-mentioned streptococci. S. suis is thus a paradigmatic example of possible intersections between animal and human resistomes.